Hygiene Sanitasi dan Keberadaan Bakteri Escherichia Coli pada Depot Air Minum (DAM) - Peronika Deliana Elsa; Riyan Ningsih; Sitti Badrah (Buletin Keslingmas, 2025)
Drinking safe water is essential for public health, yet challenges remain in meeting this need, particularly in developing regions. In Indonesia, while 93% of the population has access to improved water sources, only 11,9% receive safe drinking water. Refill water depots are the primary source of drinking water for households; however, studies have reported significant contamination risks, including Escherichia coli, often due to poor hygiene and sanitation practices. This study examines the relationship between hygiene and sanitation practices and the presence of E. coli in refill water depot in Sempaja Selatan. Using a descriptive quantitative method with a cross-sectional observational approach, the study analyzed five refill water depots identified with E. Coli contamination in 2023. Data collection included direct observations, interviews, and laboratory testing of water samples. Results revealed no. E. coli contamination in any samples, reflecting improvements in sanitation and hygiene practices, such as regular equipment maintenance and adherence to personal cleanliness by operators. However, 60% of depots still fail to meet hygiene and sanitation standards, particularly in personal hygiene and raw water quality management. Although No. bivariate analysis was conducted due to homogeneous data, the findings highlight the importance of health regulations to ensure water safety. Future research should expand the sample size and explore external factors influencing water quality.